Head Injury: A strand in the ‘Weave’ of multiple health - morbidity in people in prison - Tom McMillan (Advances in Clinical Neuroscience & Rehabilitation)
The likelihood of a prisoner in the UK having a history of head injury is high with many having persisting disability. The characteristics of head injury are linked to challenging backgrounds and high social deprivation and are part of a complex ‘weave’ of multiple health morbidities. There is a case for head injury being a cause of criminal behaviour, although its high occurrence alone indicates a need for attention. Potential ways forward in relation to education, support and intervention for prisoners and training of staff are discussed.